Flagellin Is Required for Host Cell Invasion and Normal Salmonella Pathogenicity Island 1 Expression by Salmonella enterica Serovar Paratyphi A - Elhadad, Dana (Infect Immun, 2015)
Salmonella enterica serovar Paratyphi A is a human-specific serovar that, together with Salmonella enterica serovar Typhi and Salmonella enterica serovar Sendai, causes enteric fever. Unlike the nontyphoidal Salmonella enterica serovar Typhimurium, the genomes of S. Typhi and S. Paratyphi A are characterized by inactivation of multiple genes, including in the flagellum-chemotaxis pathway. Here, we explored the motility phenotype of S. Paratyphi A and the role of flagellin in key virulence-associated phenotypes. Motility studies established that the human-adapted typhoidal S. Typhi, S. Paratyphi A, and S. Sendai are all noticeably less motile than S. Typhimurium, and comparative transcriptome sequencing (RNA-Seq) showed that in S. Paratyphi A, the entire motility-chemotaxis regulon is expressed at significantly lowers levels than in S. Typhimurium. Nevertheless, S. Paratyphi A, like S. Typhimurium, requires a functional flagellum for epithelial cell invasion and macrophage uptake, probably in a motility-independent mechanism. In contrast, flagella were found to be dispensable for host cell adhesion. Moreover, we demonstrate that in S. Paratyphi A, but not in S. Typhimurium, the lack of flagellin results in increased transcription of the flagellar and the Salmonella pathogenicity island 1 (SPI-1) regulons in a FliZ-dependent manner and in oversecretion of SPI-1 effectors via type three secretion system 1. Collectively, these results suggest a novel regulatory linkage between flagellin and SPI-1 in S. Paratyphi A that does not occur in S. Typhimurium and demonstrate curious distinctions in motility and the expression of the flagellum-chemotaxis regulon between these clinically relevant pathogens.